How does the World Bank fund leveraging resources to improve the reach and uptake of feed and forage innovations? - Mekonnen, Kindu; Gebreyes, Million; Bezabih, Melkamu; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Presented at a consultative meeting with the World Bank evaluation team, Addis Ababa, Ethiopia, 29 January 2024. Nairobi, Kenya: ILRI.